Development of a Web-Based Information System for Heavy Equipment Rental at CV. Amelia Putri Using the CodeIgniter Framework - Sigit Auliana; Amelia, Nur; Aryono, Gagah Dwiki Putra (Jurnal Sistem Komputer dan Informatika (JSON), 2025)
The development of information technology demands digital transformation in business management, including the heavy equipment rental sector. CV Amelia Putri, which still uses a manual recording system, faces various operational obstacles such as data errors, administrative inefficiencies, and slow customer service. This research aims to design a web-based heavy equipment rental information system using the CodeIgniter framework to overcome these problems. The research methodology uses a qualitative approach with SWOT analysis and waterfall development method. The system is designed with Model-View-Controller architecture integrated with MySQL database and XAMPP supporting technology. The results showed that the system succeeded in increasing operational efficiency by 80% and data accuracy reached 95%. The main features include user registration, tool search, online ordering, admin verification, payment management, and automated reporting. Black Box Testing proves that all modules function optimally with a high level of user satisfaction. The implementation of this digital system not only reduces recording errors and speeds up administrative processes, but also significantly improves operational transparency and customer service quality.